Analisis pengembangan hidrokinetik turbin gorlov akibat penambahan luas bidang tangkap - Try Antomo; I Made Kamiana; Dwi Anung Nindito (Jurnal Teknika, 2020)
Turbin gorlov merupakan salah satu teknologi turbin hidrokinetik yang berbeda dengan turbin air konvensional. Turbin gorlov dapat dipasang secara vertikal maupun horizontal dan mampu digunakan pada kondisi low-head, namun memiliki luas bidang tangkap yang bergantung dari dimensi lengkung bilah heliks. Hidrokinetik turbin gorlov digunakan sebagai pembangkit listrik tenaga hidro dengan memanfaatkan energi kinetik dari aliran air sungai maupun pasang surut. Turbin DNA merupakan jenis turbin baru hasil pengembangan desain turbin gorlov dengan cara menambahkan komponen pair yang bertujuan menambah luas bidang tangkap ()A. Studi ini dilakukan dengan membandingkan performa yang dihasilkan turbin gorlov dan turbin DNA. Pengujian dilakukan pada saluran prismatik dengan variasi kecepatan aliran 0,188 – 0,222 m/s. Pengaruh penambahan luas bidang tangkap ()A. f dengan melakukan penambahan komponen pair menyebabkan penurunan performa CPf dan  pada desain turbin DNA. Turbin gorlov menghasilkan tip-speed ratio () 2,11 – 2,24, dan coefficient of power ()C 0,26 – 0,30. Turbin DNA menghasilkan tip-speed ratio () dengan range 0,91 – 1,07 dan coefficient of power ()C 0,19 – 0,24. Rotasi per menit (RPM) yang dihasilkan dari turbin gorlov dan turbin DNA masing-masing adalah 31,1 – 38,1 dan 13,0 – 17,6. Torsi () turbin gorlov dan turbin DNA masing-masing adalah 0,025 – 0,038 Nm dan 0,054 – 0,085 Nm. Pengaruh penambahan luas bidang tangkap dengan penambahan komponen pair menyebabkan rotasi per menit (RPM) turbin DNA mengalami penurunan, akan tetapi memiliki keunggulan dalam nilai torsi () yang dihasilkan. Hal ini terlihat dari kecenderungan grafik torsi () terhadap penambahan kecepatan aliran pada sudut rotasi 0    90, 120    210 dan 240    330. The Gorlov turbine is a hydrokinetic turbine technology different from conventional water turbine. It can be mounted vertically or horizontally and also be used in low-head conditions however, it has a frontal area which depends on the curved dimensions of helical blade. Hydrokinetic turbines are used for hydroelectric power plants by converting kinetic energy from river and tidal streams. The DNA turbine is a new type of turbine developed by Gorlov turbine design with the addition of pair components aiming toincrease the frontal area ()A. This study compared performance of Gorlov turbine and DNA turbine. The testing was carried out on a prismatic channel with a flow velocity variation of 0.188 - 0.222 m/s. The effect of increasing frontal area  performance on DNA turbine design. Gorlov turbine produced a tip-speed ratio f ()A with the addition of pair components caused a decrease in f() 2.11 - 2.24 and coefficient of power  ()C of 0.26 - 0.30. DNA turbine produced tip-speed ratio P() of 0.91 - 1.07 and coefficient of power ()C value of 0.19 - 0.24. The rotation per minute (RPM) values resulting from Gorlov turbine and DNA turbine were 31.1 - 38.1 and 13.0 - 17.6, respectively. Torque P () of Gorlov turbine and DNA turbine were 0.025 - 0.038 Nm and 0.054 - 0.085 Nm, respectively. The effect of increasing frontal area ()A with the addition of pair components caused the rotation per minute (RPM) of the DNA turbine to decrease. However, it had an advantage in the resulting torque value. This could bes een from the graphical trend of torque value 0 90   , f 120 210    and () to the increase in the flow velocity at rotation angles of 240 330   .  The Gorlov turbine is a hydrokinetic turbine technology different from conventional water turbine. It can be mounted vertically or horizontally and also be used in low-head conditions however, it has a frontal area which depends on the curved dimensions of helical blade. Hydrokinetic turbines are used for hydroelectric power plants by converting kinetic energy from river and tidal streams. The DNA turbine is a new type of turbine developed by Gorlov turbine design with the addition of pair components aiming to increase the frontal area ()A. This study compared performance of Gorlov turbine and DNA turbine. The testing was carried out on a prismatic channel with a flow velocity variation of 0.188 - 0.222 m/s. The effect of increasing frontal area  performance on DNA turbine design. Gorlov turbine produced a tip-speed ratio f ()A with the addition of pair components caused a decrease in f() 2.11 - 2.24 and coefficient of power ()C of 0.26 - 0.30. DNA turbine produced tip-speed ratio P () of 0.91 - 1.07 and coefficient of power ()C value of 0.19 - 0.24. The rotation per minute (RPM) values resulting from Gorlov turbine and DNA turbine were 31.1 - 38.1 and 13.0 - 17.6, respectively. Torque P() of Gorlov turbine and DNA turbine were 0.025 - 0.038 Nm and 0.054 - 0.085 Nm, respectively. The effect of increasing frontal area ()A with the addition of pair components caused the rotation per minute (RPM) of the DNA turbine to decrease. However, it had an advantage in the resulting torque value. This could be seen from the graphical trend of torque value 0 90   , f 120 210    and () to the increase in the flow velocity at rotation angles of 240 330   .